Dashboard of intelligent transportation system (ITS) using mobile agents strategy on notification authentication process - Najia Allali; Zineb Chaouch; Mohammed Tamali (Institute of Advanced Engineering and Science, 2019)
Extracting accurate information from huge Transportation Database need to build efficiency Intelligent Transportation Systems ITS-Dashboard that should allow making correct decisions. The quality of decision and the achievement of performance depend on the quality of the information supplied. This information must be reliable, complete, pertinent and more to care about external attacks. Distributed Mobile Agent consists of autonomy of entities with capacities of perception, cooperation and action on their own environment. One of Agent function is the security of Authentication process by activation of notification system on Mobile Device. The main purpose of this paper is to make it consisting of an Agent Based Framework. The strategy is to exploit Mobile Agent capabilities in a Strict Notification Process when user validates his authentication request.